Utilization of Financial Statements Information Systems of Kopwan "Anugerah Bersama" at Gunung Anyar Tambak Surabaya - Kustini; Ira Wikartika (Nusantara Science and Technology Proceedings)
Community service activities through the program of utilization of science and technology for the community (PIKAT) has been done in women's cooperative "Anugerah Bersama" which is a cooperative managed by housewives in the village of Anyar Tambak Gunung Kota Surabaya. This program is a continuation of the activities that have been done in 2016 regarding the making of financial statements namely balance sheet, business results report, and cash flow statement. This community service program is funded by LPPM Universitas Pembangunan Nasional “Veteran” Surabaya, East Java, Indonesia’s self-funded Universitas Pembangunan Nasional “Veteran” Surabaya, East Java, Indonesia year 2017. The program's activities are carried out by way of public education and training to the women's cooperative managers. The purpose and benefits of this program is to provide knowledge to the public about the importance of cooperatives for the community to improve welfare and train the skills of cooperative managers about how to use financial cooperative accounting software that later can simplify and accelerate the preparation of savings or savings accounts for members of the cooperative. With the counseling is expected to increase the number of members of the cooperative so that will strengthen the cooperative capital and limit the movement of moneylenders in the future. The results obtained from this training are the cooperative managers have been able to create savings reports using cooperative financial accounting software easily, quickly, and precisely.